2018
DOI: 10.1089/end.2018.0134
|View full text |Cite
|
Sign up to set email alerts
|

Trifecta Outcomes in Multifocal Tumors: A Comparison Between Robotic and Open Partial Nephrectomy

Abstract: Surgical resection remains the mainstay for patients with unilateral, synchronous, and multifocal renal tumors. Our analysis found that both open and robotic approaches to partial nephrectomy are equally likely to achieve the "trifecta" outcome in an equilibrated high-risk group of patients. The robotic approach for these complex patients may be safe and feasible for a carefully selected group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…As in our study, Yerram et al [15] found that achievement of the trifecta outcome (de ned as negative surgical margins, no urologic complications, and ≥ 90% eGFR preservation at last follow-up) was not different between OPN and RAPN. This may be explained by the fact that LPN is inferior to both surgical OPN and RAPN because of its more challenging surgical techniques.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As in our study, Yerram et al [15] found that achievement of the trifecta outcome (de ned as negative surgical margins, no urologic complications, and ≥ 90% eGFR preservation at last follow-up) was not different between OPN and RAPN. This may be explained by the fact that LPN is inferior to both surgical OPN and RAPN because of its more challenging surgical techniques.…”
Section: Discussionsupporting
confidence: 76%
“…As in our study, Zargar et al [20] found that the postoperative creatinine concentration and eGFR were not different between LPN and RAPN. Yerram et al [15] found that the proportion of patients with ≥ 90% eGFR preservation at follow-up was not different between OPN and RAPN.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although there are several different definitions for trifecta in the literature, the main goals of the trifecta outcomes in terms of LPN are achieving negative surgical margin, minimizing postoperative complications and WIT (22). Besides the definition of a diverse trifecta criterion, the characteristics of the patients and the tumor included in the studies, the surgical technique used and the surgical experience might have resulted in reporting disparate success rates (23,24). Therefore, the trifecta outcomes indicated in the literature vary from 32% to 81% (25).…”
Section: Discussionmentioning
confidence: 99%
“…Yerram et al. [ 12 ] compared the trifecta outcomes of 68 RAPN vs. 42 OPN in kidneys with multiple tumors. Trifecta was defined as negative surgical margins, no urologic complications, and a glomerular filtration rate (GFR) preservation of ≥90% at last follow-up.…”
Section: Pn In Complex Scenariosmentioning
confidence: 99%